A legal analysis on law and policy on conservation of forest in Peninsular Malaysia / Adzidah Binti Yaakob - Yaakob, Adzidah (2014)

(untitled)
Forest performs multiple functions and requires a diligent commitment to its conservation. This green cover in Peninsular Malaysia, although accounting for only a small percentage of the land area, shelters a unique range of biodiversity living within it. Nonetheless, this natural resource of Peninsular Malaysia appears to be dwindling, mostly as a result of the actions of humankind, even though this green cover is governed by sets of laws. The protected area, a status secured by the law, is apparently easily excised from the government gazette, and the status of permanent forest use is changed to non-permanent forest use, for instance agriculture, plantations, residential or industrial activities and projects. This study seeks to analyse the current forest conservation practices in different states of Peninsular Malaysia in order to determine whether the current practices conform to Environmental Law principles recognised at the international level. The Stockholm Declaration followed by the Rio Declaration have indeed widened the global perspectives on environmental conservation, and their impact can be seen in the current approach of forest conservators in Peninsular Malaysia; however, the amount of forest area, as shown in forest reports and statistics, is decreasing. The rights of participation in decision-making on land and forest resources by the public and Orang Asli communities (indigenous peoples) as important stakeholders in forests in Peninsular Malaysia are also discussed. Data and information from various libraries and institutions have been gathered and collected in the course of this research and study. In order to support and strengthen the arguments and discussion based on the aforementioned information and data, semi-structured interviews are conducted with the forest conservators, inter alia officers in charge of forest conservation in every State Forestry Department of Peninsular Malaysia, the Department of Orang Asli Development and Sahabat Alam Malaysia (Friends of the Earth, Malaysia) as well as the World Wide Fund for Nature, Malaysia (both are iv environmental Non-Governmental Organisations (NGO)). Officers of Department of Environment and Department of Wildlife and National Parks also assisted in providing further related data and information. From the interviews and the information given, it was evident that forest conservators and officers in charge of Orang Asli were aware of Environmental Law principles recognised at the international level; however, this awareness is not reflected in the law and policy on forest in Peninsular Malaysia. Nonetheless, the NGOs have different views on the need to revamp the forest law and policy to ensure better forest ecosystem protection. Moreover, it was also found that the National Forest Policy 1978 (Revised 1992) only stressed sustainable forest management without acknowledging other Environmental Principles, thus indicating the priority of economic purposes over environmental needs. Meanwhile, the National Forestry Act 1984 was more concerned with the administration of forest than with its environmental aspects. Hence, a comprehensive law and policy on forest that conforms to recognised Environmental Principles of forest is considered significant and vital to ensure that this unique forest, which provides thousands of benefits, can be sustained for future generations to enjoy.